Clinical Efficacy and Safety of Combination Therapy with Amlodipine and Olmesartan or an Olmesartan/Hydrochlorothiazide Compound for Hypertension: A Prospective, Open-Label, and Multicenter Clinical Trial in China - Gao, Pingjin (Curr Ther Res Clin Exp, 2015)
BACKGROUND: Amlodipine (AML) is the initial therapy most commonly prescribed for patients with hypertension in China. However, AML monotherapy is often less effective in achieving blood pressure (BP) control than other agents. OBJECTIVE: We performed a clinical study to evaluate efficacy and safety of a combination therapy with AML, olmesartan (OLM), or an OLM/hydrochlorothiazide (HCTZ) compound for Chinese patients with mild-to-moderate hypertension. METHODS: In the clinical trial, patients were initially treated with OLM 20 mg/d combined with AML 5 mg/d. Then OLM was uptitrated to 40 mg/d or changed to an OLM/HCTZ (20/12.5 mg/d) compound if the patients did not reach the target of seated diastolic BP <90 mm Hg (<80 mm Hg in patients with diabetes) after 8 weeks. RESULTS: The overall response rate of the combination therapy was 59.2% (95% CI, 54.23%–63.97%) at Week 2 and gradually increased to 97.1% (95% CI, 94.93%–98.47%) at the end of the study (Week 16). CONCLUSIONS: The combination therapy with OLM or OLM/HCTZ was well tolerated. The total incidence of adverse events was 42.9% (n = 176). Most of the adverse events were mild in severity (39.5%; n = 162) and not associated with the drugs (33.2%). In conclusion, combination therapy with AML, OLM, or OLM/HCTZ can significantly lower BP safely and achieve a high BP control rate in patients with mild-to-moderate hypertension in China. ClinicalTrial.org identifier: ChiCTR-ONC-12001963.